2006
DOI: 10.1248/jhs.52.58
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of Disinfectants: Two New Aromatic Degradation Products of Chlorhexidine, Chlorhexidine Aromatic Degradation Product (CHADP)-4 and CHADP-6, Produced by Pseudomonas sp. Strain No. A-3

Abstract: To clarify the degradation pathway of chlorhexidine by a microbe, Pseudomonas sp. Strain No. A-3, the isolation and identification of microbial chlorhexidine degradation products were attempted. Two aromatic degradation products of chlorhexidine, named chlorhexidine aromatic degradation product (CHADP)-4 and CHADP-6, were isolated by column chromatography using Diaion HP-10, and purified by column chromatography using Diaion HP-20SS and Sephadex LH-20. The chemical structures of both compounds were examined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Tanaka et al (32,33) reported that the degradation of CHX occurs through the cleavage of molecules along the hexane diamine linker between the aromatic rings at either end of the molecule. Such cleavage results in smaller degradation products, each of which contains an aromatic ring, and can cause PCA formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al (32,33) reported that the degradation of CHX occurs through the cleavage of molecules along the hexane diamine linker between the aromatic rings at either end of the molecule. Such cleavage results in smaller degradation products, each of which contains an aromatic ring, and can cause PCA formation (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the degradation of CHX occurs through the cleavage of the molecule along the hexane diamine linker between the aromatic rings at either end of the molecule (19, 20). Such cleavage results in smaller degradation products, each of which contains an aromatic ring.…”
Section: Discussionmentioning
confidence: 99%
“…Figura 2.9 -Identificação na figura de mecanismo de degradação da CLX (Figuras 2.10 e 2.11), peso molecular e estrutura molecular proposta para os compostos intermediários de degradação da clorexidina em PCA, segundo Zong (2011) Figura 2.12 -Estruturas moleculares dos compostos CHCI-B, CHCI-BR e CHCI-D, segundo Uyeda et al (1996) Figura 2.14 -Compostos da degradação da CLX e suas fragmentações em espectrometria de massa, segundo Tanaka et al (2006) …”
Section: Lista De Figurasunclassified
“…Foi demonstrado anteriormente que a degradação de CLX ocorre através da quebra da molécula no grupo guanidil ligado aos anéis aromáticos em ambas as extremidades da molécula (Tanaka et al, 2005;Tanaka et al, 2006). Essa quebra resultaria em produtos de degradação menores em massa que a CLX, cada qual contendo um grupo anilina com um átomo de cloro na posição 4.…”
Section: Nacional De Toxicologia Da Agência De Proteção Ambiental (Epunclassified
See 1 more Smart Citation